The Lost Promise of Progressivism - Eisenach, Eldon J.; Project Muse. (Lawrence, Kan. : University Press of Kansas, 1994)
This is a provocative reconsideration of the intellectual origins of Progressivism as it developed from 1885 to the eve of World War I. Eldon Eisenach argues that the Progressives are far more important for our understanding of American culture than we've been led to believe and that they, in fact, established and shaped our most influential institutions - governmental, cultural, educational, religious, professional, economic, and journalistic - as we know them today. Eisenach contends that, despite its demise as a galvanizing force in national party politics, Progressive thought remains a powerful influence in contemporary America. In particular, he shows how Progressive ideas resonate with current debates over individual rights and civic responsibilities, the relationship between the government and the economy, and America's international reputation.
Progressivism as National Regime -- The Nation as History and Destiny -- The Nation and Public Opinion -- Nation, Party Government, and Constitution -- Nation and Economy -- National Democracy and Personal Freedom -- Nation and World.
Description based on print version record.
Keywords: Progressismus; Politik; Progressivism (United States politics); Politieke ideeën.; Progressivisme; Progressivism (United States politics); Politics and government; Progressivism (United States politics); USA; United States -- Politics and government -- 20th century; United States -- Politics and government -- 1865-1933.; United States; United States -- Politics and government -- 20th century; United States -- Politics and government -- 1865-1933.; Electronic books